Decolonizing the pocket monster : Smartphones, Pokémon Go and generational conflict in Malaysian Borneo - Asmus, Rungby; Poline, Bala (SAGE Publications Inc., 2023)
This article analyzes the generational politics of smartphones in the Malaysian state of Sarawak in the context of Bornean history and contemporary Sarawakian political economy. We respond to a global north bias in the standing literature on smartphone media and suggest approaches to improve representation of global south perspectives. Concretely, we propose three programmatic maxims as a methodological guide to incorporate perspectives and concerns from the global south more fully. Drawing on long-term ethnographic research in Sarawak, we demonstrate the value of these suggestions by framing smartphones in the perspective of Bornean history as tools for maintaining instrumental social networks more than exchanging information across spatial disjunction. These tools are used differently by young urbanites and older rural populations. This leads us to show how Pokémon Go refracts generational conflicts by becoming the cultural touchstone of the changing political economic conditions of Malaysian urbanization.